Distinct signalling pathways for induction of MAP kinase activities by cadmium and copper in rice roots - Yeh, Chuan-Ming; Chien, Pei-Shan; Huang, Hao-Jen (Journal of experimental botany, 2007)
Plant growth is severely affected by toxic concentrations of heavy metals. On characterizing the heavy metal-induced signalling pathways, the effects of cadmium (CdCl2) and copper (CuCl2) on MBP (myelin basic protein) kinase activities in Oryza sativa L. cv. TNG67 were analysed and it was found that Cd2+-induced 42 kDa MBP kinase has the characteristics of a mitogen-activated protein (MAP) kinase. This study confirmed that the 42 kDa kinase-active band contains, at least, the activities of OsMPK3 and OsMPK6. Then, the heavy metal signal transduction pathways leading to MAP kinase activation in rice roots were examined. Pretreatment with sodium benzoate, a hydroxyl radical scavenger, attenuated Cd2+- or Cu2+-induced MAP kinase activation. The Cd2+-, but not Cu2+-, induced MAP kinase activities were suppressed by diphenylene iodonium (DPI), an NADPH oxidase inhibitor, and Cd2+ induced NADPH oxidase-like activities, suggesting that NADPH oxidases may be involved in Cd2+-induced MAP kinase activation. Using a Ca2+ indicator, it was demonstrated that Cd2+ and Cu2+ induce Ca2+ accumulation in rice roots. The Cd2+- and Cu2+-induced MAP kinase activation required the involvement of Ca2+-dependent protein kinase (CDPK) and phosphatidylinositol 3-kinase (PI3 kinase) as shown by the inhibitory effect of a CDPK antagonist, W7, and a PI3 kinase inhibitor, wortmannin, respectively. Furthermore, bongkrekic acid (BK), a mitochondrial permeability transition pore opening blocker, suppressed Cd2+-, but not Cu2+-, induced MAP kinase activation, indicating that Cd2+-induced MAP kinase activities are dependent on the functional state of mitochondria. Collectively, these findings imply that Cd2+ and Cu2+ may induce MAP kinase activation through distinct signalling pathways. Moreover, it was found that the 42 kDa MAP kinase activities are higher in Cd-tolerant cultivars than in Cd-sensitive cultivars. Therefore, the Cd-induced 42 kDa MAP kinase activation may confer Cd tolerance in rice plants.